Synergy of Institutional Partnerships in Realizing Village SDGs Through Utilization of Mangrove Fruits for Coffee - Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The problem in Bukit Batu District is the destruction of mangrove forests due to the logging of mangrove wood to be used as firewood, cerocok wood and charcoal wood, resulting in coastal abrasion of about 5 meters per year, even some villages in Bukit Batu District have shifted their coastline by about 200 meters. inland from the initial location due to abrasion. This incident is certainly contrary to the sustainable development goals (SDGs). Moreover, currently there is a policy that is required by the ministry of villages, development of disadvantaged areas and transmigration to all villages in Indonesia through the use of village funds to realize the Village SDGs through one of the village typologies, namely villages that care about the marine environment. The purpose of this service is to realize the Village SDGs, the village government is experiencing difficulties due to limited resources and knowledge, it is necessary to have a synergistic institutional partnership between the village government, community, universities and companies to facilitate the achievement of the Village SDGs. The method used is a participatory method by inviting people to care about the marine environment. Furthermore, providing knowledge by introducing the use of non-timber mangroves such as mangrove fruit for coffee. The success of this activity is judged by the changes in community activities and routines to preserve the mangrove ecosystem. Increasing public awareness and knowledge that mangrove ecosystems can provide social, economic and environmental benefits in accordance with sustainable development goals.